The Effectiveness of Strawberries (Fragaria x ananassa) on Extrinsic Stanins and Salivary pH - Pribawanti, Dewi Candra; Alfaini, Rosyda Aufia Sanata (Center of Excellent (Pusat Unggulan Iptek), 2026)
Background: Strawberries (Fragaria x ananassa) are a fruit plant in the form of herbs that were first discovered in Chile, America. The benefits of strawberries are used as a natural ingredient to overcome all dental and oral problems. Tooth stains are pigmented layers on the surface of the teeth, one of the aesthetic problems, usually occurring due to the adhesion of food, drink, or cigarette color that leaves a brown to black layer on the teeth, which occurs over a long period of time is difficult to remove by brushing. Objective: The purpose of this study was to determine the effectiveness of strawberries in cleaning extrinsic stains and saliva pH in the academic community of the Polytechnic Health of Jakarta I. Method: Quasi-experimental research design with a pre-post experiment approach. The sample used was 60 people. Changes in extrinsic stains were measured using the Lobene Stain Index, which measures the intensity and extent of the stain, as well as a combined score of both, then measuring the pH of saliva using litmus paper. Results: The average combined score was 5.03. The extrinsic stain score after strawberry application showed an average combined score of 2.23. After analysis using the Dependent T test (paired test) and a p-value of 0.01. Meanwhile, the results of the saliva pH analysis obtained a p-value of 0.01 (P<0.05). Conclusion: There was a decrease in the extrinsic stain score after treatment and it showed that strawberry extract could affect saliva pH